Implementation of the ABCD5E Learning Model and Integration of 21st Century Competences in Aisyiyah Pesantunan Kindergarten, Kab. Brebes - Kur'aini, Kiki; Formen, Ali (Jurusan PGPAUD FIP UNNES, 2023)
This study aims to analyze the implementation of the ABCD5E learning model and the integration of 21st century competencies which include planning, implementation, and evaluation. In addition, knowing the supporting and inhibiting factors in the implementation of the ABCD5E learning model and the integration of 21st century competencies in Aisyiyah Pesantunan Kindergarten, Kab. Brebes. The subjects in this study were teachers, students of TK Aisyiyah Pesantunan, Kab. Brebes as well as GTK Core and GTK Partners of the ABCD5E learning model. This study uses qualitative methods, through interview techniques, observation and documentation. Then the validity is carried out by triangulating sources and techniques. The results of the study show that the teacher has implemented the ABCD5E learning model which includes planning, implementation and evaluation, each of which has its own characteristics. In learning planning, it has special characteristics in its learning objectives, namely containing elements of ABCD (Audience, Behavior, Condition, and Degree). In the implementation of learning, the teacher includes the 5E phase (Engagement, Explanation, Exploration, Elaboration and Evaluation) in the evaluation using the STAR technique. The implementation of the ABCD5E learning model can integrate in stimulating children to achieve 21st century competence (4C) in Aisyiyah Pesantunan Kindergarten. The results of the study also show that there are several supporting and inhibiting factors, namely the existence of good collaboration from school stakeholders, as well as the availability of existing infrastructure, media, tools and learning materials. While the inhibiting factor is that there are teachers who still lack knowledge about the ABCD5E learning model and limited ideas in making learning activities that are in accordance with 21st century competencies (4C).